Malignant melanoma representing with testicular metastasis: a case report and review of the literature - Aslam, Muhammad Z.; Ahmed, M.S.; Nagarajan, Sri; Rizvi, Syed T. (Canadian Urological Association Journal, 2013)
We present the case of a 52-year-old man, with a history of malignant melanoma, who presented with a testicular lump. Radical orchidectomy confirmed a metastatic malignant melanoma. We discuss salient features of this disease in the light of the published literature.